DIABETES PREVENTION PROGRAM (DPP): A PROGRAM OF THE CDC, TARGETING PRE-DIABETICS IN JOHNSON COUNTY - Garcia, Bianca (My University, 2019)
The prevalence of type 2 diabetes is rapidly increasing due to much higher incidence of new cases. In the United States, 30.3 million people are living with diabetes (“A Snapshot,” 2019). Risk factors for diabetes include having a family history of diabetes, age, being overweight, and getting little or no physical activity. To prevent or delay type 2 diabetes, a greater focus needs to be placed on lifestyles changes including weight loss and physical activity (“DTTAC,” 2017). This public health issue was my area of focus during my time at the Johnson County Department of Health and Environment (JCDHE). While at JCDHE, I assisted with the Diabetes Prevention Program (DPP). DPP is a program of the Centers for Disease Control and Prevention (CDC). This is a year-long lifestyle change program designed to prevent type 2 diabetes in prediabetic adults. Groups of 10-15 participants go through the CDC-approved curriculum as a group and focus on nutrition, physical activity, stress management and problem solving. A trained lifestyle coach facilitates the course. The goal of the program is to help participants lose 5 to 7 percent of starting body weight and increase physical activity minutes to 150 per week (“Prevent T2,” 2018). I helped JCDHE’s registered dietitian and health educator with this course, by preparing materials prior to class and assisting with the facilitation of the course. Each class included 20 minutes of health education and the rest of open-ended discussion of progress, barriers and tools to overcome obstacles. What was found from the data showed overall weight loss in the participants analyzed. Also, by addressing barriers at each level of the social ecological framework, there was an increased likelihood that participants would continue making progress towards their goals. Understanding and interpreting health behavior theories also allowed us to improve or address self-efficacy, health attitudes, social norms, and perceptions of behavior change.
Keywords: diabetes; type-2 diabetes; diabetes prevention program